Clinical characteristic of dengue fever and dengue hemorrhagic fever among patients at Sanglah Hospital, Denpasar, Bali - Shabrina Inderjit; I Made Sudarmaja; I Kadek Swastika (DiscoverSys Inc., 2021)
Background: Mosquito-borne diseases are one of the most significant public health risks globally, and dengue fever seems to be one of the most important arboviral diseases in humans. In humans, dengue viruses are the supreme agents that cause dengue fever (DF) and dengue hemorrhagic fever/dengue shock syndrome (DHF/DSS). Following that, the virus's presence, sufficient numbers of susceptible populations, and mosquito vectors are required to transmit dengue infection. This study aimed to identify the clinical characteristics of dengue fever and dengue hemorrhagic fever among patients at Sanglah Hospital, Denpasar, BaliMethod: The study is a descriptive retrospective study design. The data was collected from the medical records of patients diagnosed with dengue and dengue hemorrhagic fever in Sanglah Hospital, Denpasar, Bali, from June 2015- June 2016. We took 50 patients according to sample size calculation by randomized sampling technic. Data were analyzed descriptively.Result: The study found the age range from 5 to 53 years old. The mean age for DF and DHF were 11 and 31, respectively. Secondly, the proportion of gender in this research was male by 21 (42%) and 29 (58%) female. Further to this, Denpasar showed the maximum number of cases between all the nine regencies. Both DF and DHF cases recorded the highest total cases in April 2016.Conclusion: Expected clinical characteristics prior knowledge and prognosticators of DF and DHF development will be able to provide data to detect persons who are higher risk category and provide adequate time to clinicians to lessen dengue related morbidity and mortality